2013
DOI: 10.1089/jmf.2012.2719
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and Anti-Inflammatory Activities of Sargassum wightii and Halophila ovalis Sulfated Polysaccharides in Experimental Animal Models

Abstract: The present study investigated the effects of sulfated polysaccharides from brown seaweed Sargassum wightii (Sw-SP) and seagrass Halophila ovalis (Ho-SP) in nociceptive and inflammatory models. In the formalin test, Sw-SP and Ho-SP significantly reduced licking time in both phases of the test at a dose of 10 mg/kg. In the hot plate test, the antinociceptive effect was observed only in animals treated with 10 mg/kg of Sw-SP and 5, 10 mg/kg of Ho-SP, suggesting that the analgesic effect occurs through a central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The sulfated polysaccharides from the brown seaweeds Sargassum wightii and Halophila ovalis (Yuvaraj et al, 2013) and the red seaweeds Gracilaria cornea (Coura et al, 2012) and Caulerpa racemosa (Ribeiro et al, 2014) have anti-inflammatory activities in vivo. In a BV2 microglia cell model, Park et al (2011) demonstrated that the anti-inflammatory activity of fucoidan (a sulfated polysaccharide) from the brown seaweed Fucus vesiculosus occurred by suppressing activation of nuclear factor-kB (NF-kB) and downregulating the mitogen-activated protein kinase (MAPK) and Akt pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The sulfated polysaccharides from the brown seaweeds Sargassum wightii and Halophila ovalis (Yuvaraj et al, 2013) and the red seaweeds Gracilaria cornea (Coura et al, 2012) and Caulerpa racemosa (Ribeiro et al, 2014) have anti-inflammatory activities in vivo. In a BV2 microglia cell model, Park et al (2011) demonstrated that the anti-inflammatory activity of fucoidan (a sulfated polysaccharide) from the brown seaweed Fucus vesiculosus occurred by suppressing activation of nuclear factor-kB (NF-kB) and downregulating the mitogen-activated protein kinase (MAPK) and Akt pathways.…”
Section: Introductionmentioning
confidence: 99%
“…PLSs have a number of biological properties, including antinociceptive [Yuvaraj et al, ], anti‐inflammatory [Batista et al, ], and gastroprotective activities [Silva et al, ]. However, no studies to date have linked the therapeutic potential of CG to gastrointestinal (GI) tract disorders associated with NSAID use.…”
Section: Introductionmentioning
confidence: 99%
“…Crude sulfated polysaccharide was extracted from brown seaweed S. wightii and seagrass H. ovalis as described previously. [ 9 ] Purification was achieved on successive solubilization and precipitation of the biopolymer in aqueous medium. Water and enzyme extracted polysaccharide was applied to a diethylaminoethyl (DEAE)–cellulose column (20 cm × 2 cm) equilibrated with 50 mM sodium chloride solution.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, sulfated polysaccharides of seaweeds and seagrasses have gathered unprecedented attention in recent times being a prolific source of natural analgesic and anti-inflammatory agents. [ 7 8 9 ] The sulfated polysaccharides from Sargassum species have been explored for possible anti-inflammatory effects. [ 10 11 ] In general, chemical characteristics such as molecular size, sugar composition, sulfate content, type of linkage, and molecular geometry have a great influence on their biological activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation